Effects of tofacitinib monotherapy on patient-reported outcomes in a randomized phase 3 study of patients with active rheumatoid arthritis and inadequate responses to DMARDs. Issue 1 (December 2015) - Strand, Vibeke; Kremer, Joel; Wallenstein, Gene; Kanik, Keith; Connell, Carol; Gruben, David; Zwillich, Samuel; Fleischmann, Roy
Abstract Introduction Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis. Method In this 6-month, phase 3, randomized, placebo-controlled trial, 611 patients with inadequate response to disease-modifying anti-rheumatic drugs (DMARD-IR) were randomized 4:4:1:1 to receive: tofacitinib 5 mg BID or tofacitinib 10 mg BID for the duration of the study, or placebo for 3 months followed by tofacitinib 5 mg BID or tofacitinib 10 mg BID. Patient-reported outcomes (PROs) included: Patient Global Assessment of Disease Activity (PtGA); Patient Assessment of Pain (Pain); Health Assessment Questionnaire-Disability Index (HAQ-DI); Medical Outcomes Survey (MOS) Short Form-36 (SF-36); Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F); and MOS Sleep Scale. Time-to-event data (PtGA and Pain) were collected using an interactive voice response system daily diary (baseline through day 14). Results At month 3, tofacitinib 5 and 10 mg BID demonstrated statistically significant improvements versus placebo in PtGA (bothp < 0.0001), Pain (bothp < 0.0001), HAQ-DI (bothp < 0.0001), SF-36 Physical (p < 0.0001) and Mental (p < 0.05 [5 mg BID] andp < 0.0001 [10 mg BID]), Component Summary scores and all domain scores (p < 0.05–p < 0.0001) and FACIT-F (bothp < 0.0001). Statistically significant changes from baseline in MOS Sleep Scale were reported for 10 mg BID (p < 0.05). Benefits of tofacitinib treatment were rapid in onset and significant improvements were reported at week 2 for PtGA, Pain and HAQ-DI, and differentiation from baseline was seen as early as 3 days after treatment initiation for interactive voice response system (IVRS) PtGA and IVRS Pain. The numbers needed to treat for patients to report changes greater than or equal to the minimum clinically important difference in PtGA, Pain, HAQ-DI, SF-36 Physical Component Summary score and FACIT-F ranged between 4.0–6.1 (5 mg BID) and 3.2–5.0 (10 mg BID). Conclusion Tofacitinib monotherapy in DMARD-IR patients resulted in statistically significant and clinically meaningful improvements in multiple PROs versus placebo at month 3, with sustained improvements over 6 months. Trial registration Clinicaltrials.gov registrationNCT00814307, registered 22 December 2008